Perencanaan Sistem Pengelolaan Sampah Skala Desa di Kecamatan Mukok Kabupaten Sanggau - Sugeng, Try Kurniadi; Jumiati, Jumiati; Desmaiani, Herda (Universitas Trunojoyo Madura, 2025)
Population growth in Mukok District, Sanggau Regency, and West Kalimantan Province has resulted in the expansion of residential areas that are difficult to access by local government waste disposal facilities. The enormous volume of waste is the result of the community's lack of understanding of the significance of appropriate waste management and disposal. Burning rubbish is a common sanitary practice. The purpose of this research is to investigate the current waste management system in Mukok District, estimate the expected waste volume till 2032, and build an effective waste management system for Mukok District. The collection and measurement of waste samples adhere to the SNI 19-3694-1994 criteria. Inggis, Semuntai, and Kedukul villages generate 2.66 m3/day, 9 m3/day, and 3.05 m3/day of rubbish, respectively. The waste management plan calls for isolating organic and inorganic trash at the source, using individual containers for each residence, and collecting trash on a daily basis with three-wheeled bike.